Evidence Supporting an Association Between Expression of Major Histocompatibility Complex II by Microglia and Optic Nerve Degeneration During Experimental Glaucoma. Issue 8 (August 2016) - Chidlow, Glyn; Ebneter, Andreas; Wood, John P.M.; Casson, Robert J.
Abstract : Aim: We acquired age-matched and sex-matched Sprague-Dawley rats from 2 independent breeding establishments. Serendipitously, we observed that constitutive, and bacterial toxin–induced, expression of major histocompatibility complex (MHC) class II RT1B chain in the uveal tract was much lower in one of the cohorts. Activated microglia are known to upregulate MHC II RT1B expression during optic nerve (ON) degeneration induced by raised intraocular pressure (IOP). We investigated whether, in a model of experimental glaucoma, microglial upregulation of MHC II RT1B was less efficacious and ON degeneration correspondingly less severe in the cohort of rats with low MHC II RT1B expression. Methods: Experimental glaucoma was induced by lasering the trabecular meshwork using a standard protocol. After 2 weeks of elevated IOP, retinal ganglion cells (RGC) survival, ON degeneration, and microglial responses were determined in both cohorts of rats. Results: Raised IOP-induced expression of MHC II RT1B by microglia was muted in the "Low" cohort compared with the "High" cohort. Axonal degeneration, RGC loss, and microgliosis were all significantly lower in the cohort of rats with low basal and induced expression of MHC II RT1B, despite both cohorts displaying IOP responses that were indistinguishable in terms of peak IOP and IOP exposure. Conclusions: Expression of MHC II RT1B by activated microglia in the ON during experimental glaucoma was associated with more severe RGC degeneration. Further studies are needed to elucidate the role of MHC II during experimental glaucoma.